Human capital, employment and bargaining - Hart, Robert A. 1946-; Moutos, Thomas 1960- (Cambridge Univ. Press, 1995)
Labour market policy topics recur throughout the book and include the choice between pure wage and profit sharing remuneration systems, the issue of whether training should be subsidised by governments, worksharing versus layoff decisions, payroll tax incidence and the choice of compensation system as well as the role of human capital in influencing a firm's voluntary ex ante decision as to whether or not to bargain with an established union
Keywords: Collectieve onderhandelingen; Emploi; Human Capital; Négociations collectives; Ressources humaines; Werkgelegenheidsbeleid; Human capital; Employment (Economic theory); Collective bargaining; Arbeitslosigkeit; Arbeitsbeziehungen; Beschäftigung; Lohntheorie; Humankapital